Grounding Speech Acts: The Humanist Capital of National Hero TGKH. Muhammad Zainuddin Abdul Madjid - Siti Ainun Hasanah; Rhoma Dwi Aria Yuliantri (El Harakah)
Effective character education needs to be contextualized in real life to have a significant impact. TGKH Muhammad Zainuddin Abdul Madjid is a national hero from Lombok, West Nusa Tenggara who becomes a prominent figure on character education. This research discusses how TGKH directly demonstrates character education through his daily speech acts to students, congregation, and the surrounding community. The research method used is a historical method which consists of four stages: heuristics, source verification, data interpretation, and historiography. It used a lot of primary sources in the form of oral interviews. The research results show that character education by TGKH. Muhammad Zainuddin Abdul Madjid was built through direct examples through everyday words and actions, how to reprimand students who make mistakes, providing direct examples of doing things, and simple speech acts in everyday life. His teaching was very influential in the internalization of character education that emphasized on the importance of example in everyday words and actions. This shows that a practical and personal approach to character education has a significant impact on shaping moral and ethical values in society. These speech act strategies offer valuable insights into leadership, education, and community engagement.